2014
DOI: 10.1186/1556-276x-9-696
|View full text |Cite
|
Sign up to set email alerts
|

Passivation ability of graphene oxide demonstrated by two-different-metal solar cells

Abstract: The study on graphene oxide (GO) grows rapidly in recent years. We find that graphene oxide could act as the passivation material in photovoltaic applications. Graphene oxide has been applied on Si two-different-metal solar cells. The suitable introduction of graphene oxide could result in obvious enhancement on the efficiency. The simple chemical process to deposit graphene oxide makes low thermal budget, large-area deposition, and fast production of surface passivation possible. The different procedures to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…Solar energy is considered a possible alternative to the traditional fossil fuel energy sources due to the fact that the sun is essentially a free and continuous energy supply. Additionally, the cost of solar cells can be dramatically reduced when the efficiency of solar cells is increased; for example, a solar module that exhibited a 1% enhancement in its efficiency led to a 5% reduction in price . G/GO exhibits potential as an optically conductive window as they allow a wide range of light wavelengths to pass through, that is, optical transmittance reaching ∼98%. , Additionally, G/GO optical and electrical properties can be modulated through noncovalent interactions with metal complexes, which make it suitable for different types of solar cell applications. Wang et al’s group have developed a solution-based low-temperature deposition procedure to manufacture the electron collection layer using a G/TiO 2 nanoparticle material as the electron collection layers in meso-superstructured perovskite solar cells.…”
Section: Applications Of Noncovalently Functionalized Graphene and Gr...mentioning
confidence: 99%
See 4 more Smart Citations
“…Solar energy is considered a possible alternative to the traditional fossil fuel energy sources due to the fact that the sun is essentially a free and continuous energy supply. Additionally, the cost of solar cells can be dramatically reduced when the efficiency of solar cells is increased; for example, a solar module that exhibited a 1% enhancement in its efficiency led to a 5% reduction in price . G/GO exhibits potential as an optically conductive window as they allow a wide range of light wavelengths to pass through, that is, optical transmittance reaching ∼98%. , Additionally, G/GO optical and electrical properties can be modulated through noncovalent interactions with metal complexes, which make it suitable for different types of solar cell applications. Wang et al’s group have developed a solution-based low-temperature deposition procedure to manufacture the electron collection layer using a G/TiO 2 nanoparticle material as the electron collection layers in meso-superstructured perovskite solar cells.…”
Section: Applications Of Noncovalently Functionalized Graphene and Gr...mentioning
confidence: 99%
“…Additionally, the cost of solar cells can be dramatically reduced when the efficiency of solar cells is increased; for example, a solar module that exhibited a 1% enhancement in its efficiency led to a 5% reduction in price . G/GO exhibits potential as an optically conductive window as they allow a wide range of light wavelengths to pass through, that is, optical transmittance reaching ∼98%. , Additionally, G/GO optical and electrical properties can be modulated through noncovalent interactions with metal complexes, which make it suitable for different types of solar cell applications. Wang et al’s group have developed a solution-based low-temperature deposition procedure to manufacture the electron collection layer using a G/TiO 2 nanoparticle material as the electron collection layers in meso-superstructured perovskite solar cells. They found that the solar cells manufactured using this low-temperature process exhibit a significant photovoltaic performance, that is, power conversion efficiency up to 15.6%, which suggests that solar cells no longer need a high-temperature sintering process when TiO 2 is employed in the electron collection layer (see Figure ).…”
Section: Applications Of Noncovalently Functionalized Graphene and Gr...mentioning
confidence: 99%
See 3 more Smart Citations